UPLC–MS/MS method for the simultaneous quantification of three new antiretroviral drugs, dolutegravir, elvitegravir and rilpivirine, and other thirteen antiretroviral agents plus cobicistat and ritonavir boosters in human plasma - Simiele, Marco; Ariaudo, Alessandra; De Nicolò, Amedeo; Favata, Fabio; Ferrante, Martina; Carcieri, Chiara; Bonora, Stefano; Di Perri, Giovanni; D’Avolio, Antonio (Journal of pharmaceutical and biomedical analysis, 2017)
Typical chromatogram from direct injection of a chemical mix containing all the target analytes at a concentration of 2μg/mL. [Display omitted] •Useful UHPLC–MS/MS method to quantify a wide panel of antiretroviral drugs.•Validated method following FDA guidelines.•Fast and cheap protein precipitation protocol, suitable for clinical routine.•The method has been tested on real-life specimens with good results. Rilpivirine (RPV), dolutegravir (DTG) and elvitegravir (EVG) are the latest antiretroviral drugs approved for treatment of HIV infection. Currently, poor information is currently available concerning their pharmacokinetic and pharmacodynamic properties, thus making the use of therapeutic drug monitoring for these drugs not useful. This lack of information is partially due to the absence of an high-throughput method for their simultaneous quantification together with other antiretroviral drugs. In this work, we describe the development and validation of a new UPLC–MS/MS method to quantify these drugs, together with other fourteen antiretroviral agents, in human plasma. One hundred microliters of plasma samples were added with internal standard (6,7-Dimethyl- 2,3-di(2-pyridyl) quinoxaline), underwent a simple protein precipitation with methanol:acetonitrile (50:50v/v) followed by sample dilution with water. Chromatographic separation was performed on a Acquity® UPLC HSS T3 column (150mm x 2.1mm I.D) with a particle size of 1.8μm and compounds were detected with a tandem mass detector, monitoring two ion transitions for each drugs. The mean recovery of RPV, DTG and EVG were 101%, 87% and 112.3% respectively. Accuracy and precision inter/intra-day were below 15% for all drugs, in accordance to Food and Drug Administration guidelines requirements. The UPLC–MS/MS method reported here could be used routinely to monitor plasma concentrations of antiviral drugs, including RPV, DTG and EVG.